Endoscopic mucosal resection/endoscopic submucosal dissection for gastric heterotopic pancreas - Yun-Shi ZHONG; Qiang SHI; Li-Qing YAO; Ping-Hong ZHOU; Mei-Dong XU; Ping WANG (Turkish Journal of Gastroenterology, 2019)
-